2021
DOI: 10.1002/ptr.7243
|View full text |Cite
|
Sign up to set email alerts
|

Rosa Damascena mill for treating adults' anxiety, depression, and stress: A systematic review and dose–response meta‐analysis of randomized controlled trials

Abstract: Recent studies have reported conflicting findings on the antianxiety, antidepressant, and anti-stress properties of Rosa Damascena Mill (RDM). Therefore, the present systematic review and meta-analysis were conducted on the effects of RDM for treating anxiety, depression, and stress amongst adults. The online data sources of Cochrane Central Register of Controlled Trials, PubMed, Scopus, Web of Science, Embase, ProQuest, and Scientific Information Database were searched from inception to June 30, 2021. The ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Despite the fact that R. damascena has been evaluated in recent systematic reviews for anti‐anxiety (Rasooli et al, 2021), pain‐relieving (Nasiri, Torkaman, Feizi, & Shamloo, 2020), and sleep‐enhancing properties (Rami et al, 2021), no reviews have ever summarized R. damascena 's mechanisms of action in the treatment of mental disorders based on preclinical animal studies and clinical trial assessments. Saffron (Talaei, Moghadam, Tabassi, & Mohajeri, 2015), valerian ( Valeriana officinalis ), Cinnamon ( Cinnamomum zeylanicum ), Banafsha ( Viola Odorata ), Echium ( Echium amoneum ) (Bakhshaei, 2017) have been reported for the treatment of anxiety disorders and depression in PTM, but none of them were emphasized as much as Rosa damascena .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that R. damascena has been evaluated in recent systematic reviews for anti‐anxiety (Rasooli et al, 2021), pain‐relieving (Nasiri, Torkaman, Feizi, & Shamloo, 2020), and sleep‐enhancing properties (Rami et al, 2021), no reviews have ever summarized R. damascena 's mechanisms of action in the treatment of mental disorders based on preclinical animal studies and clinical trial assessments. Saffron (Talaei, Moghadam, Tabassi, & Mohajeri, 2015), valerian ( Valeriana officinalis ), Cinnamon ( Cinnamomum zeylanicum ), Banafsha ( Viola Odorata ), Echium ( Echium amoneum ) (Bakhshaei, 2017) have been reported for the treatment of anxiety disorders and depression in PTM, but none of them were emphasized as much as Rosa damascena .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that R. damascena has been evaluated in recent systematic reviews for anti-anxiety (Rasooli et al, 2021), pain-relieving (Nasiri, Torkaman, Feizi, & Shamloo, 2020), and sleep-enhancing properties (Rami et al, 2021), no reviews have ever summarized R. damascena's mechanisms of action in the treatment of mental disorders based on preclinical animal studies and clinical trial assessments.…”
Section: Discussionmentioning
confidence: 99%
“…The psychometric properties of the Persian version of STAI-S have been confirmed by previous investigations [ 46 ]. Also, it is a commonly used tool by Iranian scholars [ 47 ], and its reliability was reported as acceptable among patients with burns [ 17 , 28 ]. In the present study, the coefficient of Cronbach’s alpha for this tool was 0.91.…”
Section: Methodsmentioning
confidence: 99%
“…A search request with "Rosa damascena AND essential oil" on pubmed.ncbi.nlm.nih.gov resulted in 40 results in the last 10 years (accessed on 21.09.2023 22 : 59). Concerning psychiatric issues like anxiety, depression, stress [137], and insomnia [138], metaanalyses are available. Furthermore, pain [139] and sexual dysfunctions [140,141] are research topics.…”
Section: Rose Oilmentioning
confidence: 99%
“…Clinical studies on the effect of R. damascena oil inhalation or oral intake on psychiatric disorders make up a large proportion of the studies found in the literature. A meta-analysis concluded that the inhalation or oral intake of R. damascena oil influenced state anxiety, depression, and stress positively [137]. Even in exceptional situations, damask rose oil decreased state anxiety and improved sleep, as a randomized controlled trial on inhalation aromatherapy in operating room personnel reported during the COVID-19 pandemic [142].…”
Section: Psychological Effectsmentioning
confidence: 99%